Demethylation of an NF-κB enhancer element orchestrates iNOS induction in osteoarthritis and is associated with altered chondrocyte cell cycle. Issue 11 (November 2016) - de Andrés, M.C.; Takahashi, A.; Oreffo, R.O.C.
Summary: Objective: To examine the methylation profile of the nuclear factor (NF)-κB enhancer region at −5.8 kb of inducible nitric oxide synthase ( iNOS ) and the subsequent role in the induction of osteoarthritis (OA) via cell cycle regulation. Methods: Percentage methylation was determined by pyrosequencing, gene expression by qRT-PCR and cell proliferation was determined using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Transient transfections were induced to determine the effect of the NF-κB enhancer region on cell proliferation and the influence of DNA methylation. Results: In vitro de-methylation with 5-aza-dC showed decreased levels of DNA methylation at CpG sites localised at −5.8 kb, which correlated with higher levels of iNOS expression. In vitro methylation of the NF-κB enhancer region at −5.8 kb increased the percentage of cells at G0/G1 cell cycle phase. Loss of methylation within this region correlated with, enhanced proliferation and increased number of cells at G2/M phase. OA chondrocytes demonstrated up-regulation of the G0/G1 cell cycle progression markers Cyclin D1 and CDK6 in contrast to control cells. We demonstrate the loss of methylation that occurs at specific CpG sites localised at the −5.8 kb NF-κB enhancer region of the iNOS gene in OA chondrocytes permits the binding of this transcription factor activating the expression of iNOS . This results in subsequent altered cell cycle regulation, altered proliferative phenotype and transmission of the pathogenic phenotype to daughter cells. Conclusions: This study indicates that inhibition of cell cycle progression by iNOS enhancer hypermethylation is capable of reducing pro-inflammatory responses via down-regulation of NF-κB with important therapeutic implications in OA.